Examining the Effects of Afterschool Reading Interventions for Upper Elementary Struggling Readers. (May 2018) - Roberts, Garrett J.; Capin, Philip; Roberts, Greg; Miciak, Jeremy; Quinn, Jamie M.; Vaughn, Sharon
We examined the efficacy of an afterschool multicomponent reading intervention for third- through fifth-grade students with reading difficulties. A total of 419 students were identified for participation based on a 90 standard score or below on a screening measure of the Test of Silent Reading Efficiency and Comprehension. Participating students were randomly assigned to a business as usual comparison condition or one of two reading treatments. All treatment students received 30 min of computer-based instruction plus 30 min of small-group tutoring for four to five times per week. No statistically significant reading comprehension posttest group differences were identified ( p > .05). The limitations of this study included high attrition and absenteeism. These findings extend those from a small sample of experimental studies examining afterschool reading interventions and provide initial evidence that more instruction, after school, may not yield the desired outcome of improved comprehension.